Development of a DNA-based diagnostic method to detect sugarcane bacterial pathogens with emphasis on Clavibacter xyli subsp. xyli - Van Antwerpen, Tania (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.